IGF2BP3 Regulates TMA7-mediated Autophagy and Cisplatin Resistance in Laryngeal Cancer via m6A RNA Methylation - Like Yang; Bingrui Yan; Lingmei Qu; Jingyuan Ren; Qiuying Li; Jingting Wang; Xuan Kan; Ming Liu; Yakun Wang; Yanan Sun; Chao Wang; Peng Wang (2023)
Translation machinery associated 7 homolog (TMA7) is closely related to proliferation-related diseases. However, the function and regulatory mechanism of TMA7 in laryngeal squamous cell carcinoma (LSCC) remain unclear. The present study aimed to investigate the effect of TMA7 on the occurrence and development of LSCC and to study the mechanism of TMA7. TMA7 is upregulated in LSCC tissues and associated with poor prognosis. After TMA7 downregulation, the autophagy level was increased, and the proliferation, migration, and invasion of LSCC cells were inhibited. The m6A methylated reader IGF2BP3 enhanced the stability of TMA7 and reduced the level of autophagy. TMA7 interacted directly with UBA2. Furthermore, the activation of the IGF2BP3-regulated TMA7-UBA2-PI3K pathway is the primary mechanism by which TMA7 inhibits autophagy and promotes the progression of LSCC. The current study revealed that IGF2BP3-mediated TMA7 m6A modification promotes LSCC progression and cisplatin-resistance through UBA2-PI3K pathway, providing new insights into the autophagy-related mechanism, potential biomarkers, and therapeutic targets for LSCC.